Usability of Screencast in 1st Basic Physics Lectures During the Covid-19 Pandemic: Student’s Perception Analysis - Ernita Susanti; Rahmat Rizal; Dwi Sulistyaningsih (Jurnal Ilmiah Pendidikan Fisika, 2021)
The enactment of Work from Home (WFH) during the Covid-19 pandemic has affected educational activities. Conventional offline learning must be held online so that effective online learning media is needed. The screencast is an online learning media that believed can provide easy access to students in conducting an online lecture. The screencast is a digital video recording on the computer screen and usually includes audio narration. This study aimed to analyze students' perception on screencast use in 1st Basic Physics lectures during the Covid-19 pandemic. This research involved 76 physics education students in one of the higher education institutions in Tasikmalaya. They consist of 9 males and 67 females in the age range (18-21 years). This research is a descriptive study, with data collection techniques using a Likert scale questionnaire. Analysis of students' perceptions of screencast aspects (content, construct, language, and graphic) are good, with a value of 79. Then, analysis of screencast implications on changes in students' knowledge and skills are a good category with a value of 78. The analysis of students' perceptions found a positive response using screencast in 1st Basic Physics lecture. The screencast can be effective online learning media to enhance student's knowledge and skills